Graphene nanoplatelets-reinforced polyetherimide foams prepared by water vapor-induced phase separation - H. Abbasi (eXPRESS Polymer Letters, 2015)
The present work considers the preparation of medium-density polyetherimide foams reinforced with variable amounts of graphene nanoplatelets (1–10 wt%) by means of water vapor-induced phase separation (WVIPS) and their characterization . A homogeneous closed-cell structure with cell sizes around 10 µm was obtained, with foams exhibiting zero crystallinity according to X-ray diffraction (XRD). Thermogravimetric analysis under nitrogen showed a two-step thermal decomposition behaviour for both unfilled and graphene-reinforced foams, with foams containing graphene presenting thermal stability improvements, related to a physical barrier effect promoted by the nanoplatelets. Thermo-mechanical analysis indicated that the specific storage modulus of the nanocomposite foams significantly increased owing to the high stiffness of graphene and finer cellular morphology of the foams. Although foamed nanocomposites displayed no further sign of graphene nanoplatelets exfoliation, the electrical conductivity of these foams was significant even for low graphene contents, with a tunnel-like model fitting well to the evolution of the electrical conductivity with the amount of graphene.